Influencia de la dosificación de cloro y peróxido de hidrógeno sobre el contenido final de cianuro total en el tratamiento de aguas en minera yanacocha s.r.l. - Carranza López, Junior Fernando (2016)
In the present investigation was to study the influence dosing of hydrogen peroxide and chlorine on the final content of total cyanide, the effluent from the reverse osmosis plant at Yanacocha Norte - Yanacocha SRL, applying a two-factor design. The variable dosage of hydrogen peroxide was evaluated in levels (0,13; 0,15 and 0,17) g/l dose of chlorine variable levels were evaluated (0,03; 0,05 and 0,07) g/l. Nine combinations was performed with the values of the variables, and each combination was repeated three times, making a total of 27 tests. Each test was carried out with 1 000 ml of sample. The results indicated that the content lowest total cyanide, namely than 0,06 ppm is obtained at a hydrogen peroxide dosage of 0,17 g/l of chlorine to 0,07 g /l. From the results of the analysis of the final effluent can conclude that with increasing dosage of hydrogen peroxide (0,13 to 0,17) g/l, total cyanide final content decreases, it is observed that for , likewise observed that increasing the dosage of chlorine of (0,03 to 0,07) g/l total cyanide final content decreases. Finally at a confidence level of 95%, the analysis of variance confirms that the variables are significantly affecting both study, the dosage of hydrogen peroxide and chlorine, being demonstrated the economic feasibility of using these reagents in the detoxification of mining effluents. Keywords: Detoxification, reactive content, effluent, dosing.